Tecnologías para museos virtuales en dispositivos móviles - María Dolores Robles Ortega; Francisco R. Feito Higueruela; Juan José Jiménez Delgado; Rafael J. Segura Sánchez (Virtual Archaeology Review)
Virtual museums have incorporated new contents which make the knowledge transmission easier, thanks to the development of the new technologies. Evidently, it would be desirable that all these new elements could be accessed using any mobile device. In this paper we study the main graphical languages to create 3D virtual museums and the process to adapt it to mobile devices. Specifically, we focus on the following technologies: Flash, VRML and X3D. We also explain the initial process to migrate the Virtual Museum of Iberian Art developed in a previous work in order to be renderized using a Samsung Galaxy Tab 10.1 with Android as operative system.